Scanning electron microscope observation on tegumental damage of 21-d-old Schistosoma japonicum induced by praziquantel - XIAO Shu-hua; SHEN Bing-gui (Acta Pharmacologica Sinica; Vol 16, No 3 (May 1995): Acta Pharmacologica Sinica, 2016)
AIM: To study the effect of praziquantel (Pra) on the tegument of 21-d-old schistosomula, mice infected with Schistosoma japonicum cercariae for 21 d were treated ig with Pra at a single dose. METHOD: Groups of mice were killed at different intervals within 48 h, and the worms were collected by perfusion for scanning electron microscopic observation. RESULTS: When the dose used was 300 mg.kg(-1), the worms showed mild or moderate swelling, fusion or even erosion and collapsed of the tegumental ridges, which was characterized by swelling of the discoid sensory structures. At higher dose of 500 mg.kg(-1), similar alterations in the worm surface were seen, but more extensive and serious. When Pra 500 mg.kg(-1) was given daily for 3 d, severe swelling, erosion and peeling of the tegument accompanied by the attachment of the host leukocytes on the damaged surface were seen. CONCLUSION: Pra exhibited a direct killing effect on 21-d-old schistosomula.